Membrane lipid raft organization is uniquely modified by n-3 polyunsaturated fatty acids - Turk, Harmony F. (2012)
Fish oil, enriched in bioactive n-3 polyunsaturated fatty acids (PUFA), has been shown to play a role in prevention of colon cancer. The effects of n-3 PUFA are pleiotropic and multifaceted, resulting in an incomplete understanding of their molecular mechanisms of action. Here, we focus on a highly conserved mechanism of n-3 PUFA, which is the alteration of the organization of the plasma membrane. We highlight recent work demonstrating that enrichment of n-3 PUFA in the plasma membrane alters the lateral organization of membrane signaling assemblies (i.e. lipid rafts). This mechanism is central for n-3 PUFA regulation of downstream signaling, T-cell activation, transcriptional activation, and cytokine secretion. We conclude that these studies provide strong evidence for a predominant mechanism by which n-3 PUFA function in colon cancer prevention.